EFEK PROTEKSI MENGKUDU (Morinda citrifolia L.)TERHADAP JUMLAH SPERMATID TESTIS MENCIT (Mus musculus) YANG DIPAPAR ASAP ROKOK - Larassuci, Fitria Dewi; Annisah, Fitroh; Aviani, Rifki; Rizky, Syifa Marhattya; Nurhidayah, Siti (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Free radicals of the cigarette smoke can decrease the male fertility. In present study, Morinda citrifolia L. extract was evaluated for its protective effect on the number of spermatids which induced by cigarette smoke in Swiss webster mice. Four groups of mice were arranged as follows: KK (control group), KP0 (cigarette smoke), KP1(low dose extract + cigarette smoke), KP2 (high dose extract + cigarette smoke). After 14-day treatment, all mice were sacriï¬ced. The LSD test showed significant differences between each pair of groups. Morinda citrifolia L. extract showed protective effect to the number of spermatids which induced by cigerette smoke.Â Keywords: Morinda citrifolia L. extract, cigarette smoke, number of spermatids